Lactogenic Potential of Banana Flower (Musa spp.) on Breast Milk Production: A Systematic Review - Fitria Mushollini; Aprilya Roza Werdani; Fitratur Rahmah Agustina; Samnil Astuti Fitri; Donal Ortega (Fakultas Kedokteran, Universitas Papua, 2025)
Inadequate breast milk production is a major contributor to the failure of exclusive breastfeeding. Banana flower (Musa spp.) has long been traditionally used as a galactagogue in Southeast Asia; however, its clinical effectiveness requires systematic evaluation. This systematic review aims to evaluate the lactogenic effects of banana flower on breast milk production based on available clinical evidence. A systematic search was conducted in ProQuest, ScienceDirect, and Portal Garuda databases for studies published between 2016 and 2026. The inclusion criteria comprised randomized controlled trials (RCTs) and quasi-experimental studies involving postpartum mothers. Results: Thirteen studies were identified for synthesis. The majority of quasi-experimental studies conducted in Indonesia reported a significant increase in breast milk volume (p < 0.05) following the consumption of fresh banana flower (200–300 g/day). In contrast, high-quality RCTs using encapsulated extracts demonstrated inconsistent findings, with some studies reporting no significant differences compared with placebo during the early postpartum period. These discrepancies may be attributed to variations in banana species (e.g., Musa balbisiana), processing methods, and dosage. Phytochemical compounds such as saponins and flavonoids present in banana flower are hypothesized to stimulate prolactin secretion. Conclusion: Banana flower shows promising potential as a natural galactagogue, particularly when consumed as a whole food. However, standardized RCTs with precise dosing are required to confirm its clinical applicability.